Out of the picture? How incompatible knowledge and distant visual stimuli may foster idea generation. (10th April 2019) - Brun, Juliette; Le Masson, Pascal; Weil, Benoit
Abstract : Visual stimuli such as pictures, sketches or prototypes play a major role in idea generation. Companies today often promote the use of these non‐verbal tools during creativity sessions, at the early stages of design. However, recent studies tend to show that these tools do not systematically enhance idea generation. Our research project therefore aims to better understand the contribution of visual stimuli during creativity sessions, and especially the contribution of distant stimuli which present knowledge that appears to be incompatible with the design topic. This study is based on an exploration led at the automotive company Renault by a team working on new services for charging electric vehicles. During idea generation sessions, a set of pictures was used by a meeting facilitator to inspire the team with new ideas. We show that the effects produced by the different pictures are varied: they do not always promote radical expansion, and when they do, expansion is not always of the same nature. Moreover, represented knowledge appears to have a major influence on idea generation, as the most original ideas came from pictures that not only expanded initial knowledge, but also helped to reorder the team's knowledge base and introduce new design rules.